The Experience of Revelation in the Islamic Religion - Brînzea, Nicolae; Morcov, Elena (Technium Social Sciences Journal, 2023)
The concept of revelation is the fundamental basis of the great belief systems, being articulated and proclaimed within them. This manifestation of divinity then becomes the basis of authority in the religious realm. Religious authority refers to the divine right to introduce or impose upon people a system of beliefs, practices, or values. Islam claims its origins in the Abrahamic tradition and claims to preserve the true faith that Abraham professed. Islam states that it is based on the Abrahamic tradition and that it aims to preserve the true faith that Abraham professed. In this context, Islam aims to establish an authentic monotheism, excluding later developments of doctrine that might affect the original Abrahamic monotheism.